The prophylactic total gastrectomy paradigm in gastric cancer: background to evaluate its therapeutic scope - Celis Rubio, Pablo; Berenguela Mazo, Alina; Berrezueta Ocaranza, Diego; González Sandoval, Antonia (Revista Chilena de Estudiantes de Medicina, 2024)
Gastric cancer (GC) is the fifth most common cancer worldwide and stands as the leading cause of cancer-related mortality in men in Chile. Its etiology remains unknown, with identified risk factors including Helicobacter pylori (HP) infection and a family history of GC. Within the spectrum of hereditary gastric cancer (HGC), Hereditary Diffuse Gastric Cancer (HDGC) stands out, characterized by mutations in CDH1 that have been extensively studied. Prophylactic total gastrectomy (PTG) is recognized as the optimal preventive and therapeutic approach for CDH1-related HDGC. However, the first estimate of the cumulative risk of developing CGDH in patients carrying CTNNA1 mutations was recently established, and the possibility of performing PTG has also been raised. Concurrently, multiple other pathogenic genetic variants and factors, such as Amerindian ancestry and HP infection, have been described as significantly elevating the risk of GC development. This review aims to describe the leading genetic causes of GC and HGC, focusing on HDGC, and to present evidence supporting the use of PTG in asymptomatic patients carrying mutations other than CDH1, such as CTNNA1 or presenting a high cumulative risk due to the interaction of CTNNA1 or other pathogenic genetic variants with HP infection and/or the potential risk of their ancestry, encouraging the development of future research to promote this indication.